2013
DOI: 10.2147/dddt.s43930
|View full text |Cite
|
Sign up to set email alerts
|

S-nitroso-N-acetylcysteine attenuates liver fibrosis in experimental nonalcoholic steatohepatitis

Abstract: S-Nitroso-N-acetylcysteine (SNAC) is a water soluble primary S-nitrosothiol capable of transferring and releasing nitric oxide and inducing several biochemical activities, including modulation of hepatic stellate cell activation. In this study, we evaluated the antifibrotic activity of SNAC in an animal model of nonalcoholic steatohepatitis (NASH) induced in Sprague-Dawley rats fed with a choline-deficient, high trans fat diet and exposed to diethylnitrosamine for 8 weeks. The rats were divided into three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Yang et al reported that the expression of HSP60 was significantly upregulated in the liver tissue of mice with liver fibrosis and that this upregulation was reversed by a miR-29a mimic ( 49 ). Mazo et al also revealed that the expression of HSP60 mRNA was significantly increased in a rat model of nonalcoholic steatohepatitis, whereas S-nitroso-N-acetylcysteine decreased the expression of HSP60 and COL1A1 and alleviated liver fibrosis ( 50 ). HSP60 is mainly involved in protein transport and folding under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported that the expression of HSP60 was significantly upregulated in the liver tissue of mice with liver fibrosis and that this upregulation was reversed by a miR-29a mimic ( 49 ). Mazo et al also revealed that the expression of HSP60 mRNA was significantly increased in a rat model of nonalcoholic steatohepatitis, whereas S-nitroso-N-acetylcysteine decreased the expression of HSP60 and COL1A1 and alleviated liver fibrosis ( 50 ). HSP60 is mainly involved in protein transport and folding under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 was found to regulate PPARγ activity in a mouse model of NAFLD, and its overexpression in cells could increase neutral lipid accumulation [ 5 ]. Previous studies have revealed that S-nitroso-N-acetylcysteine attenuated liver fibrosis in experimental non-alcoholic steatohepatitis via a mechanism that involved HSP60 downregulation [ 13 ]. HSP70, an informative representative of the HSP gene family, was recently found to be decreased in the liver and adipose tissue of obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of macrophage infiltration, a pro-inflammatory state develops in visceral adipose tissue. Activation of TLR4 receptors in Kupffer cells and hepatocytes further activates and phosphorylates NF-κB, which induces cytokine and chemokine production by NOD-like receptor thermal protein domain-associated protein 3 (NLRP3) inflammatory vesicles (Mazo et al, 2013). These cytokines/chemokines accelerate the progression of non-alcoholic fatty liver to NASH by binding to specific receptors in the hepatocytes and immune response cells and then promoting inflammation and hepatocyte apoptosis.…”
Section: Potential Synergistic Mechanism Of Curcumin On the Transitio...mentioning
confidence: 99%